Reservas extractivas ¿Alternativa para la conservación de especies forestales? - Pérez-García, Martha; Rebollar Domínguez, Silvia (Instituto de Ecología, A.C., 2016)
Extractive reserves represent a recently developed strategy to protect forest areas continuosly subject  to extraction of non-wood forest products. This kind of protected area was originally developed in Brazil because of  the rubber tappers needs to diminish the continuous and fast loss of large forest areas of the Amazonas, while extracting Para rubber (Hevea brasiliensis [ Willd. Ex Adr. Juss.] M. Arg. ) Brazil nuts (Bertholletia excelsa Humb. & Bonpl.) and other forest products. Extractive reserves strategy was incorporated in the Brazilian law in 1990, and currently they are avoiding the reduction of the deforestation rates. In Mexico this concept was applied in 1910 at the Maya area of Quintana Roo state. Because chicle market decreased, this kind of reserve area moderated the communitary extraction activities of other forest products and avoided drastic land use change of important tropical forest areas. In this paper we discuss the relevance of extractive reserves strategy in terms of its functionality to reduce the effects of deforestation in tropical rain forest areas.  We conclude that this kind of protected area has limitations and should be considered as an alternative only to extract non-wood forest products in low quantities while containing the tropical rain forest areas deforestation.